1161 MIGRAINE AND SLEEP: A BI-DIRECTIONAL ASSOCIATION. (28th April 2017) - Mackus, M; Kraneveld, AD; Garssen, J; Verster, JC
Abstract: Introduction: One of the factors that has been considered to trigger migraine attacks is poor sleep. Research has shown that both the lack of sleep, and excessive sleep can provoke migraine. Alternatively, headache and migraine itself may cause sleep disturbances. The aim of the current study was to gain more insight in this bi-directional relationship between migraine and sleep. Methods: Dutch university students were recruited to participate in an online survey on general health. To assess possible migraine complaints, the Migraine Screen Questionnaire (MS-Q) was completed. The MS-Q consists of 5 questions, assessing frequency and characteristics of headache. Perceived sleep quality was rated from 0 (very poor) to 10 (excellent), and total sleep time and number of nightly awakenings were recorded. Further the subscales on insomnia, narcolepsy, and circadian rhythm disorder of the SLEEP-50 questionnaire were completed. Nonparametric Spearman correlations were computed to examine the relationship between MS-Q scores and the sleep outcomes. Results: N=1566 subjects completed the MS-Q and SLEEP-50 subscales. The total MS-Q score correlated significantly with the SLEEP-50 subscales on insomnia (r=0.178; p=0.000), circadian rhythm disorder (r=0.068; p=0.007), and narcolepsy (r=0.148; p=0.000), as well as the number of nightly awakenings (r=0.124; p=0.000) and perceived sleep quality (r=-0.153; p=0.000). total sleep time was not significantly associated with MS-Q scores. Conclusion: Albeit modest, significant correlations were observed between migraine scores and sleep outcomes. Migraine is associated with poor sleep quality, which is illustrated by the significantly increased number of nightly awakenings with higher migraine scores. It must be examined to what extent poor sleep is a cause or a consequence of migraine, or both. Future research should also address how improved sleep hygiene and adequate sleep habits may reduce the chances of having migraine attacks. Support (If Any): The study was funded by Utrecht University.